Dental specialty, career preferences and their influencing factors among final year dental students in Saudi Arabia - Hassan Suliman Halawany; Abdullah Salman Binassfour; Waleed Khalid AlHassan; Rami Ayed Alhejaily; Nassr Al Maflehi; Vimal Jacob; Nimmi Biju Abraham (Elsevier, 2017)
Objective: The purpose of this study was to investigate evolving trends in dental post graduate specialty preferences and career aspirations among final year dental students in Saudi Arabia. Materials and methods: A cross sectional survey using a self-administered questionnaire was conducted among final year dental students from seventeen universities in Saudi Arabia. The questionnaire enquired about socio-demographic details and the ranking of three of their best preferences among the list of specialties/general dentistry and career options. They were also enquired about their opinion regarding the total time required to become a dentist and their intention to go for further studies abroad. The questionnaire assessed factors influencing their choices using a 5 point Likert scale ranging from extremely important to not important. Binary logistic regression to examine the combined effect of several independent variables on the likelihood of choosing a dental specialization/general dentistry and career option were analyzed. Results: The overall response rate was 64.6%. Restorative and Aesthetic Dentistry was the most preferred specialty (n = 98; 17.7%) followed by Endodontics (n = 78; 14.1%); Prosthodontics (n = 65; 11.7%) and Orthodontics (n = 63; 11.4%). The two most preferred careers were 'Civilian dentist in public sector' followed by 'Academic services dentist'. Overall, students reported that the influence of family members in the dental profession, preference for private practice and specific interest in patient population as the most important factors in choosing a specialty/general dentistry. Intellectual content of the specialty was ranked the least important. On the other hand, the most important factors for choosing a career were variety of non-clinical duties, access to child care facilities and research opportunities. Conclusion: The results of this study show the top preferred specialties and career choices which can be a baseline for establishing national policies and for the improvement of graduate programs. There seems to be a need to promote mentoring activities and provide guidance and encouragement to pre-doctoral dental students in selecting the most appropriate specialty within their capability domain. Keywords: Dental profession, Dental students, Dental career, Dental manpower, Dental specialties, Dental education